The Interplay of Entrepreneurial Innovation, Government Regulation and Performance: any Lessons for The SMEs. A Theoretical Review - Dushime, Eunice; Muathe , Stephen; Kavindah , Lucy (European Scientific Journal, ESJ, 2021)
Entrepreneurial innovation is acknowledged as a key driver for improving the productivity of small and medium-sized enterprises. The effect of innovation on performance has been extensively researched, but many have overlooked small and medium-sized enterprises and government regulations. This paper provides a study of the current theoretical and empirical literature on entrepreneurial innovation constructs, government regulations and small and medium enterprise performance. The study’s specific objectives have been to discuss the main concepts of entrepreneurial innovation, government regulation and performance related to small and medium-size firms. It also aims to establish theories that link entrepreneurial innovation and government regulations; to recommend a conceptual and methodological framework to guide future studies on the identified knowledge gaps. The study was anchored by a resource based view theory supported by dynamic capability theory, Schumpeter’s innovation theory. The study was a review of previous research on entrepreneurial innovation and firm performance. These studies seem to have centered on a direct link between innovation and performance, according to the results. Thus, it is recommended that further research incorporate the small and medium enterprise context to highlight how entrepreneurial innovation affects these enterprises and the moderating variable of government regulations.